Problems in the Translation of Phraseologisms in Bilingual Dictionaries Spanish-Chinese / Chinese-Spanish - Xiaoxiao, Lyu (Sinología hispánica. China Studies Review, 2019)
The phraseology is part of the linguistic studies on phrases, proverbs, idioms, proverbs and other units of syntax totally or partially fixed. It is the reflection of a certain tradition and idiosyncrasy of society. The native speaker recognizes the phraseological units in the praxis of speech without difficulty. However, because of their idiomaticity and the sociocultural divergence between two linguistic communities, Spanish sayings and expressions cannot always be understood by the Chinese speakers. Students of Spanish as a foreign language have difficulty recognizing the non-literal meaning of an expression, the use of this type of expression in language teaching develops communicative competence, linguistics competence, sociolinguistics and pragmatics competence. Then, when producing a bilingual dictionary, it is not enough to translate it into the target language, but rather to contrast the two languages in order to inform non-native speakers of unknown elements, such as historical and cultural backgrounds, uses, and their frequency of application, variants, etc.